Psychological Preparedness for Disaster in Terms of Self Efficacy and Religious Coping - Fa'uni, Arini Mayang; Diana, Raden Rachmy (Al-Qalb : Jurnal Psikologi Islam, 2021)
Abstract: This study aim to determine level of psychological preparedness for disaster in terms of self efficacy and religious coping. Subjects in this study were 400 people of Daerah Istimewa Yogyakarta province obtained using convenience sampling techniques. This data were collected by psychological preparedness for disaster scale with an alpha coefficient of 0,929, self efficacy scale with an alpha coefficient of 0,852, and religious coping scale with an alpha coefficient of 0,917. The result showing that : 1) there was a significant relationship between self efficacy and religious coping with psychological preparedness for disaster with a significance of 0,000 (p<0,05), with an effective contribution of 43,3% on psychological preparedness for disaster, 2) there was a positive relationship between self efficacy with psychological preparedness for disaster, with an effective contribution of 38,8% on psychological preparedness for disaster, and 3) there was a positive relationship between religious coping with psychological preparedness for disaster, with an effective contribution of 4,5% on psychological preparedness for disaster. Then, based on this research, there was a relationship between self efficacy and religious coping with psychological preparedness for disaster.